Dispersion lagrangienne dans l'estuaire moyen du Saint-Laurent. [Lagrangian dispersal in the middle St. Lawrence estuary.] - St-Onge Drouin, S. (M.Sc. Thesis, Université du Québec à Rimouski,Rimouski, Québec, Canada., 2010)
The purpose of this study was to look at the importance of hydrodynamics in the spatial distribution of a population of copepod in the Middle St. Lawrence Estuary. To do this, we used a 3D numerical model of the region. Real trajectories obtained from surface drifters have been successfully compared to modeled trajectories. Then, multiple trajectories have been generated to compute finite-time Lyapunov exponents. The results of this computation have shown that hydrodynamics must be an important factor in maintaining the separation between the two clades of the copepod Eurytemora affinis. The two genetically different clades are separated by a ridge of high FTLE values, which is assumed to be a barrier to transport. This barrier, which appears one hour after high tide, is persistent for 3 to 4 ho urs during every ebb tide. We also computed the FTLE for tracers with vertical migration based on the tidal cycle. This behavior increases the residence time of the tracers near Ile aux Grues and changes the distribution of the barri ers to transport. However, our model results showed that more detailed empirical data on swimming behavior is necessary to evaluate the impact of swimming behavior on the distribution of E. affinis. Keywords: Lyapunov, FTLE, surface drifter, Lagrangian, St. Lawrence estuary, copepod, numerica! mode!, Eurytemora affinis.